The Motley Editorial Team - Morris, Melissa (The Motley Undergraduate Journal, 2023)
Meet Dr. Maria Bakardjieva, Managing Editor, Melissa Morris, and the team of undergraduate and graduate students that have worked to build The Motley's first issue this year! Maria Bakardjieva PhD. Editor-in-Chief Dr. Maria Bakardjieva is a professor and the current Chair in Communication and Media Studies at the University of Calgary, Canada. Her research examines the social construction of communication technologies and the use of digital media in various cultural and practical contexts with a focus on user agency, critical reflexivity and emancipation. She has numerous publications in leading journals and influential anthologies. The books she has authored and co-edited include Internet Society: The Internet in Everyday Life (2005), Socialbots and Their Friends: Digital Media and the Automation of Sociality (2017), Digital Media and the Dynamics of Civil Society: Retooling Citizenship in New European Democracies (2021), and How Canadians Communicate (2004 and 2007). Between 2010 and 2013, she served as the editor-in-chief of the Journal of Computer-Mediated Communication. Her current projects investigate the role digital media play in citizen engagement and democratic participation. Dr. Bakardjieva teaches courses in communication theory and research methodology, communication technology and society, digital media and democracy. She works to promote undergraduate research activities in Communication and Media Studies and engages in knowledge mobilization and community outreach intended to advance the public understanding of issues related to Communication and Media Studies. Melissa Morris, Managing Editor Melissa Morris is the founding Managing Editor for The Motley. She is currently completing her final year of her BA (Honours) Communication and Media Studies degree. In addition to her role with The Motley, she is the Director of Student Affairs for the Students in Communications Club. In the first two years of her undergraduate degree, she published two papers in the Agora Undergraduate Journal, and won a Student Writing Award. Her current research looks at the ways political ideology and subcultural identity can be expressed through visual methods such as fashion. Her other areas of academic interest include intersectional feminist research, queer studies, and governmental policy concerning communication and media. Her experience publishing and editing with the Agora Journal spurred her passion for highlighting the ideas of student authors. This February, she will be presenting at the National Student Journal Forum. Melissa has a passion for building community and empowering students to share the depth and variety of their knowledge with others. She plans to pursue a career that brings together her passion for building community, research, and global affairs. Bray Jamieson, Assistant Editor Bray (he/him) currently serves as the Motley Undergraduate Journal's Assistant Editor. Bray is a fifth-year student completing undergraduate degrees in the disciplines of Communications (Honours) and Philosophy. His research interests primarily focus on contemporary applications and understandings of Marxist theory, the discursive representation of restaurant workers, and the rhetorical construction of political discourses. Abigail Atmadja, Communications Advisor Abigail (she/her) is the Motley Undergraduate Journal's communications coordinator, peer reviewer, and editor. She is an international, fourth-year undergraduate student working towards a Bachelor of Arts (Honours) in Communications and Media Studies. As a media scholar, her areas of expertise include critical race theory, diaspora studies, and postcolonial studies. She aspires to become a corporate communications and public relations professional specializing in brand management. Sarah Chung, Communications Coordinator Sarah (she/any) is the Motley Undergraduate Journal’s communications coordinator, peer reviewer, and editor. She is currently a third-year, prospective honours student working towards a Bachelor of Arts in Communication and Media Studies. They are experienced in various media work, and they aspire to continue pursuing research in academia. Eventually, she hopes to work in the fashion publishing industry as a journalist, copy editor, or public relations professional. Asma Bernier, Peer Reviewer Asma Bernier (she/her) is a first year Graduate student in the department of Communication and Media studies. She is one of the Motley Undergraduate Journal’s peer reviewers in addition to having her own work published in the first issue. She is currently deepening her research by exploring politics and fashion, the politicization of hijab, and social movements. Brennan Chaudry, Peer Reviewer & Peer Editor Brennan (he/him) is a first year Graduate student in the department of Communication and Media studies. He contributes as a peer reviewer and copy-editor with the Motley Undergraduate Journal. Brennan’s area of research interest is in digital media, algorithms and Marxism. He believes that communications is a discipline that grows in importance every day, and undergraduate students deserve a venue for their voices to be heard. Drew Miller, Peer Reviewer Drew Miller (he/him) is a recently graduated student with a Bachelor of Arts, with a double major in Communications & Media Studies and Psychology. He is currently a peer reviewer and editor for the Motley Undergraduate Journal. His involvement in the Motley is driven by the hopes that academic writing in the Department of Communication, Media, and Film will flourish beyond his own time at the university. Kabir Singh Bedi, Peer Reviewer Kabir (he/him) is an international, second-year student working towards a Bachelor of Arts in Communication and Media Studies. He is a peer reviewer for the Motley Undergraduate Journal. His involvement with the Motley is inspired by his engagement in various student-run organizations. He is currently exploring career options and is hoping to find something he is passionate about for the long term. Luke Pye, Peer Editor Luke Pye (he/him) is a 2nd year of his BA in Communication and Media Studies and a peer editor for the first issue of the journal. One of Luke's career goals is to work as a copyeditor for either the municipal government or a non-profit organization. With this in mind, when Luke heard about the Motley journal, he jumped at the opportunity. In his time editing for the Motley, he has seen some excellent work that he otherwise would not have been privy to, and has met some amazing authors who he can see going far in their respective studies. Luke hopes to have work of his own published in a future issue of The Motley and looks forward to seeing what amazing work will be submitted next by the Communications student body! Haley Pelletier, Peer Reviewer & Peer Editor Haley Pelletier (she/her) is in her sixth year of a combined Communications and Political Science degree. She is a peer reviewer and editor for the Motley Undergraduate Journal. Through her role with the journal, she hopes to gain formal experience in publishing, editing, and facilitating this unique undergraduate opportunity for the Communications department and its students.